ANALISIS TINGKAT KETERBACAAN BUKU SISWA BAHASA INDONESIA KELAS VII BERBASIS KURIKULUM 2013 - Gumono, Gumono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
The aim of this research is to comprehensively  describing readability of Bahasa Indoesia’s students text book. The books is “Buku Siswa Bahasa Indonesia Kelas VII” revision edition 2014,  published by Ministry of Education and Culture. Research was conducted with descriptive quantitative design. All of text in the text book (38 article) was taken as sample, and analysed using Fry Graph formula.  The result of analysis shown, more than a half of all text (52%) is suitable for seventh grade student. While, 18 text  (48%) is not suitable one.